Demonstration of Rickettsia Conorii-Induced Coagulative and Platelet Activation in vivo in Patients with Mediterranean Spotted Fever - Davì, Giovanni; Giammarresi, Carlo; Vigneri, Sergio; Ganci, Antonina; Ferri, Claudio; Di Francesco, Letizia; Vitale, Giustina; Mansueto, Serafino (Thrombosis and Haemostasis, 1995)
Endothelial injury in vivo induced by Rickettsia Conorii, the etiologic agent of Mediterranean Spotted Fever (MSF) has been recently demonstrated. We sought to determine whether platelet and/or coagulative activation in vivo can be demonstrated in the acute phase of MSF, through measurements of a major metabolite of thromboxane (TX) in the urine (1 1-dehydro-TXB2) and of plasma prothrombin fragment 1+2, whose levels reflect activation of prothrombin to thrombin. Moreover, we measured plasma endothelin-1 as marker of endothelial dysfunction. Our results provide biochemical evidence for the occurrence of TXA2-dependent platelet activation and thrombin generation in vivo, together with endothelial dysfunction. These phenomena could account for clinical manifestations of MSF, such as vasculitis and focal microthrombus formation. These results could also provide a rationale for testing the efficacy of aspirin or heparin in reducing the prothrombotic status of Rickettsiae diseases.